2020
DOI: 10.1021/acs.organomet.0c00683
|View full text |Cite
|
Sign up to set email alerts
|

Cooperativity in Highly Active Ethylene Dimerization by Dinuclear Nickel Complexes Bearing a Bifunctional PN Ligand

Abstract: In order to examine the possibility to promote cooperative effects on catalytic activity and selectivity in ethylene dimerization through ligand design, the bisphosphino-iminato ligands syn- L and anti- L were prepared to support the dinuclear nickel complexes syn -Ni 2 and anti- Ni 2 . The Ni centers are successfully locked in relatively close proximity in syn- Ni 2 (6.433(5) Å) but are much farther apart in anti- Ni 2 because of the rigid anthracene skeleton. The mononuclear complex [NiBr2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 74 publications
0
13
0
Order By: Relevance
“…The conden-sation reaction was catalyzed by p-TsOH in methanol at room temperature to give the desired NNO-tridentate ligands LH1-LH6 in high yields (77-95%). 58,59 All the organic ligands were characterized by 1 H and 13 C NMR (Fig. S1-S12 †), and elemental analysis.…”
Section: Synthesis and Characterization Of Ligands And Chromium Compl...mentioning
confidence: 99%
“…The conden-sation reaction was catalyzed by p-TsOH in methanol at room temperature to give the desired NNO-tridentate ligands LH1-LH6 in high yields (77-95%). 58,59 All the organic ligands were characterized by 1 H and 13 C NMR (Fig. S1-S12 †), and elemental analysis.…”
Section: Synthesis and Characterization Of Ligands And Chromium Compl...mentioning
confidence: 99%
“…Up to now, the limited selectivity observed with nickel-based catalysts is mainly rationalized through a Cossee–Arlman mechanism with the active species featuring a Ni–H or Ni–C bond. , Nonetheless, only few nickel catalysts have been reported to be highly selective in ethylene dimerization to butenes/1-butene. In these cases, the precise mechanism has not been studied, yet, in general, catalysts that follow a metallacyclic mechanism are known to be much more selective toward a unique 1-alkene. Moreover, it has been shown that nickel was able, with activated alkenes such as tetrafluoroethylene (TFE), norbornadiene, or dimethylcyclopropene, to achieve an oxidative coupling to reach metallacyclic complexes (Scheme , top). In addition, Grubbs showed that butenes can be obtained from a mixture of (Cy 3 P) 2 NiCl 2 and 1,4-dilithiobutane, through the proposed decomposition of the nickellacyclopentane . Binger reported one year after that an isolated nickellacycle yielded 1-butene upon heating at 165 °C (Scheme , bottom) …”
Section: Introductionmentioning
confidence: 99%
“…Among them, hydrogen bonding represents an appropriate tool [10][11][12], as it is evidenced by biological systems in which the combination of π-stacking and hydrogen bonds determines the macrostructure of proteins or nucleic acids, just to mention well-known examples. One of the most important members of diamino PAHs is 1,5-diaminoanthracene, which is used to construct organic semiconductors [13], dinuclear nickel complexes for highly active ethylene dimerization [14], self-assembled small-molecule-based hole-transporting material for inverted perovskite solar cells [15], photoactivated healable vitrimeric copolymers [16], amorphous porous organic polymers for highly efficient iodine capture [17], bimetallic aluminum complexes for ring-opening polymerization of lactide [18], Luminescent Supramolecular Lanthanide Complexes [19], Squaraine dyes [20] and others. Despite its widespread application, the literature on the optical properties of 1,5-diaminoanthracene is very limited.…”
Section: Introductionmentioning
confidence: 99%